Dependence on Mincle and Dectin-2 Varies With Multiple Candida Species During Systemic Infection - Thompson, Aiysha; da Fonseca, Diogo M.; Walker, Louise; Griffiths, James S.; Taylor, Philip R.; Gow, Neil A. R.; Orr, Selinda J. (Frontiers in Microbiology, 2021)
More than 95% of invasive Candida infections are caused by four Candida spp. (C. albicans, C. glabrata, C. tropicalis, C. parapsilosis). C-type lectin-like receptors (CLRs) such as Dectin-1, Dectin-2 and Mincle mediate immune responses to C. albicans. Dectin-1 promotes clearance of C. albicans, C. glabrata, C. tropicalis and C. parapsilosis, however dependence on Dectin-1 for specific immune responses varies with the different Candida spp. Dectin-2 is important for host immunity to C. albicans and C. glabrata, and Mincle is important for the immune response to C. albicans. However, whether Dectin-2 drives host immunity to C. tropicalis or C. parapsilosis, and whether Mincle mediates host immunity to C. glabrata, C. tropicalis or C. parapsilosis is unknown. Therefore, we compared the roles of Dectin-2 and Mincle in response to these four Candida spp. We demonstrate that these four Candida spp. cell walls have differential mannan contents. Mincle and Dectin-2 play a key role in regulating cytokine production in response to these four Candida spp and Dectin-2 is also important for clearance of all four Candida spp. during systemic infection. However, Mincle was only important for clearance of C. tropicalis during systemic infection. Our data indicate that multiple Candida spp. have different mannan contents, and dependence on the mannan-detecting CLRs, Mincle and Dectin-2 varies between different Candida spp. during systemic infection.